Morphological variations of the thyroid gland - Veerahanumaiah, Savitha; Dakshayani, K. R.; Menasinkai, Sharada B. (International Journal of Research in Medical Sciences, 2017)
Background:The knowledge of various morphological & developmental anomalies of thyroid gland will help the surgeons in better planning of safe & effective surgery. Considering these facts we studied the variations of thyroid gland. Methods:The material for the present study was collected from the department of forensic medicine, MMC & RI, Mysore, which includes 56 male and 33 female adult postmortem cadavers aged between 18 to 80 years. A dissection was carried out to expose thyroid glands & variations were observed in the morphology of thyroid gland. Results: 1) 9% of specimens had agenesis of isthmus. 2) 46% of specimens had pyramidal lobe. 3) 41% of specimens had levator glanduli thyroidae. 4) 2.24 % of specimens had accessory thyroid tissue. Conclusion:This study highlights the various morphological anomalies of the thyroid gland which forms cornerstone to safe & effective surgery.